Increased prevalence of coronary plaque in patients with psoriatic arthritis without prior diagnosis of coronary artery disease. Issue 7 (4th January 2017) - Shen, Jiayun; Wong, Ka-Tak; Cheng, Isaac T; Shang, Qing; Li, Edmund K; Wong, Priscilla; Kun, Emily W; Law, Mei Yan; Yip, Ronald; Yim, Isaac; Ying, Shirley; Li, Martin; et al.
Abstract : Objectives: To evaluate coronary atherosclerosis in patients with psoriatic arthritis (PsA) and control subjects using coronary CT angiography (CCTA). Methods: Ninety consecutive patients with PsA (male: 56(62.2%); 50.3±11.1 years) were recruited. 240 controls (male: 137(57.1%); 49.6±10.7 years) without known cardiovascular (CV) diseases who underwent CCTA due to chest pain and/or multiple CV risk factors were recruited for comparison. Results: Patients with PsA and controls were matched in age, gender and traditional CV risk factors (all p>0.2). The prevalence of overall plaque (54(60%)/84(35%), p<0.001), calcified plaque (CP) (29(32%)/40(17%), p=0.002), mixed plaque (MP) (20(22%)/18(8%), p<0.001), non-calcified plaque (NCP) (39(43%)/53(22%), p<0.001) and combined MP/NCP (46(51%)/62(26%), p<0.001) were all significantly higher in patients with PsA. Three-vessel disease was diagnosed in 12(13%) patients with PsA and 7(3%) controls (p<0.001), while obstructive plaques (>50% stenosis) were observed in 8(9%) patients with PsA and 7(3%) controls (p=0.033). After adjusting for traditional CV risk factors, PsA remained an independent explanatory variable for all types of coronary plaques (OR: 2.730 to 4.064, all p<0.001). PsA was also an independent explanatory variable for three-vessel disease (OR: 10.798, p<0.001) and obstructive plaque (3.939, p=0.024). In patients with PsA, disease duration was the only disease-specific characteristic associated with more vulnerable plaques (MP/NCP) in multivariate analysis (1.063, p=0.031). The other independent explanatory variables were age ≥55 years (5.636, p=0.005) and male gender (8.197, p=0.001). Conclusions: Patients with PsA have increased prevalence, burden and severity of coronary atherosclerosis as documented by CCTA. Longer disease duration was independently associated with the presence of vulnerable MP/NCP plaques in patients with PsA. Trial registration number: NCT02232321 .